KONTROL DIRI SPIRITUAL SEBAGAI PREDIKTOR KEPUASAN HIDUP REMAJA: ANALISIS EFEK MEDIASI PROKRASTINASI AKADEMIK PADA SISWA SMPN 52 BANDUNG - RIPAN MAULANA; GHIFAR RAMADHAN; GANGAN SAYID MIKDAD; HADIYANTO; TARSONO (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2026)
Academic Procrastination is a critical self-regulation issue eroding the psychological well-being of adolescents. This study aims to examine the mediating role of Academic Procrastination (M) in the relationship between Spiritual Self-Control (X) and Life Satisfaction (Y) among students at SMPN 52 Bandung. Employing a quantitative approach with a correlational mediation model design, the sample consisted of 185 eighth and ninth-grade students. Data were collected using adaptations of the Spiritual Self-Control scale, the Academic Procrastination Scale, and the Satisfaction with Life Scale (SWLS), and analyzed using the PROCESS Macro (Hayes, 2018) with the Bootstrap method (5,000 samples) to test the indirect effect. The results indicate that Spiritual Self-Control positively and significantly affects Life Satisfaction (β = 0.210, p < 0.01) and negatively predicts Academic Procrastination (β = -0.380, p < 0.001). The Bootstrap test confirmed that Academic Procrastination significantly mediates the relationship (Indirect Effect = 0.173, 95% CI [0.101, 0.250]), supporting a Partial Mediation model. This finding affirms that spiritual discipline reinforced by Tarbiyah Al-Qalb (Irfani et al., 2024) and muhasabah mechanisms (Al-Ghazali, n.d.) is an effective mechanism for enhancing adolescent Life Satisfaction through the suppression of procrastination behavior. The study's implications suggest strengthening Spiritual Self-Control as a primary strategy for Guidance and Counseling services. Keywords: spiritual self-control; academic procrastination; life satisfaction; mediation analysis; junior high school.